Effectiveness of online social science undergraduate research experiences: Exploratory evidence - Ruth, Alissa; Brewis, Alexandra; SturtzSreetharan, Cindi; Wutich, Amber; Stojanowski, Christopher M. (Frontiers in Education, 2022)
Undergraduate research experiences (UREs) benefit students, but are typically conducted in person. In 2020-21, many research and teaching activities unexpectedly moved into virtual spaces. We identify key benefits and challenges experienced by virtual URE participants in the social sciences, based on systematic coding of aligned surveys with both faculty and students. Perceived benefits included access and flexibility. Both mentors and students who had switched from in-person modalities, however, expressed a perceived loss of community, undermining the perceived effectiveness and value of the URE. They also perceived the lack of “hands-on work” as a negative. In contrast, existing online students identified UREs as creating a much needed and valued connection, enhancing their experiences. We suggest the experience of all participants in virtual UREs can benefit from centralizing community-building strategies, and give some possible examples.